The External Component of National Economic Security - Bulatova, Olena; Trofymenko, Mykola; Karpenko, Oleksandr; Fedorov, Eduard (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The purpose of this paper is to determine the impact of the foreign trade component on the formation of national economic security. Transformations occurring in the world’s economic development, the deterioration of the global financial environment, and increasing geopolitical tensions have intensified the main risks to the development of the global economy in today’s conditions. Therefore, national governments are actively using a wide range of tools to ensure economic growth and the appropriate level of competitiveness of their respective economies while ensuring national security, which is relevant for the study of the external component of national economic security. To achieve the aim, general scientific and specific research methods are used, such as methods of analysis, abstraction and synthesis (in the study of protectionism as a policy and practice, instruments of neo-protectionism); methods of classification and systematic generalization (to systematize the forms of protectionism and neo-protectionism); economic and statistical methods (to assess the impact of foreign trade on the development of national economic security). It is demonstrated that the intensification of the risks to the development of the global economy has led to the transformation of trade policies, changes in the use of foreign trade regulation instruments, which affects the economic security of various countries as a major component of their national security. The modern trade and economic policy toolbox used by various countries to ensure national security is analyzed. A comparative analysis of the development of foreign trade of the EU and Ukraine has been carried out, and the features of the influence of the foreign trade component on the formation of economic security have been determined. It is demonstrated that, in the conditions of a global economic crisis, hidden forms of protectionism implemented at various levels of economic policy (global, regional, national), have spread. A classification of specific features and forms of neo-protectionism, that distinguish it from protectionism, is proposed. It is substantiated that global processes encourage national governments to implement deregulatory measures and improve the quality of institutions, while regulated economies contribute to the spread of corruption and grey areas in national economies.

Celem pracy jest określenie wpływu handlu zagranicznego na kształtowanie się bezpieczeństwa gospodarczego kraju. Przemiany zachodzące w światowym rozwoju gospodarczym, degradacja światowego otoczenia finansowego i narastające napięcia geopolityczne potęgują podstawowe zagrożenia dla rozwoju światowej gospodarki w obecnych warunkach. W związku z tym rządy aktywnie wykorzystują szeroką gamę narzędzi w celu zapewnienia wzrostu gospodarczego i odpowiedniego poziomu konkurencyjności swoich gospodarek, przy jednoczesnym zapewnieniu bezpieczeństwa narodowego, co jest istotne dla badania zewnętrznego komponentu bezpieczeństwa ekonomicznego kraju. Aby osiągnąć cel posłużono się ogólnymi metodami naukowymi i specyficznymi metodami badawczymi, takimi jak: metoda analizy, abstrakcji i syntezy (w badaniu protekcjonizmu jako polityki i praktyki oraz instrumentów neo-protekcjonizmu); metoda klasyfikacji i uogólnienia (w celu usystematyzowania form protekcjonizmu i neo-protekcjonizmu); oraz metody ekonomiczne i statystyczne (ocena wpływu handlu zagranicznego na rozwój bezpieczeństwa gospodarczego kraju). Wykazano, że nasilenie się zagrożeń dla rozwoju gospodarki światowej doprowadziło do transformacji polityk handlowych i zmian w stosowaniu instrumentów regulacji handlu zagranicznego, co wpływa na bezpieczeństwo gospodarcze krajów będące istotnym składnikiem ich bezpieczeństwa narodowego. Przeanalizowano nowoczesne instrumentarium polityki handlowej i gospodarczej, z którego korzystają państwa w celu zapewnienia sobie bezpieczeństwa. Przeprowadzono analizę porównawczą rozwoju handlu zagranicznego UE i Ukrainy oraz określono cechy wpływu komponentu handlu zagranicznego na kształtowanie się bezpieczeństwa gospodarczego. Wykazano, że w warunkach światowego kryzysu gospodarczego rozprzestrzeniały się ukryte formy protekcjonizmu, który jest stosowany na różnych poziomach polityki gospodarczej (globalnym, regionalnym, krajowym). Zaproponowano systematyzację specyficznych cech i form neo-protekcjonizmu, które odróżniają go od protekcjonizmu. Udowodniono, że procesy globalne skłaniają rządy krajowe do wprowadzania działań deregulacyjnych i poprawy jakości instytucji, a z drugiej strony regulacja gospodarki przyczynia się do rozprzestrzeniania się korupcji i rozrostu szarej strefy w gospodarkach narodowych.
Zewnętrzny komponent bezpieczeństwa gospodarczego kraju
Keywords: national security; economic security; trade and economic policy; protectionism; neo-protectionism; bezpieczeństwo narodowe; bezpieczeństwo gospodarcze; polityka handlowa i gospodarcza; protekcjonizm; neo-protekcjonizm